Experimental Set Up for Low-angle X-ray Scattering System used for the Characterization of Materials - N.A, Hussein; A, Shukri; A.A, Tajuddin (Malaysian Journal of Science, 2002)
Elastic X-ray scattering at low angles will give rise to diffraction patterns of unique signatures that can be exploited in the identification of various materials. The design criteria for setting up a low angle X-ray scattering system (LAXS) and its parameters of influence will be discussed individually. The LAXS system under construction at the School of Physics, USM, will be introduced.